1988
DOI: 10.1172/jci113818
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of serum platelet-activating factor (PAF) acetylhydrolase. Correlation between deficiency of serum PAF acetylhydrolase and respiratory symptoms in asthmatic children.

Abstract: Platelet-activating factor (PAF) acetylhydrolase has been recognized as an enzyme that inactivates PAF. We developed a convenient and reproducible method for determining human serum PAF acetyihydrolase activity. The assay was based on measurement of 1I4Clacetate produced from 1-O-alkyl-2-1'4C]-acetyl-sn-glycero-3-phosphocholine upon precipitation of the complex of radioactive substrate and albumin with TCA. The apparent Km value of PAF acetylhydrolase (near the physiological concentration of serum protein) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
116
1
4

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(128 citation statements)
references
References 39 publications
7
116
1
4
Order By: Relevance
“…Because C-PAF is slightly less potent than PAF regarding receptor binding of NP3 cells (data not shown), its metabolic stability might explain the effects different from those of PAF. Since PAF is rapidly inactivated by PAF acetylhydrolase in serum (37)(38)(39) and cytosol (40), its effect is relatively transient at low concentrations. Since C-PAF is resistant to enzymatic inactivation by virtue of the methylcarbamyl moiety at its sn-2 position, its half-life is much longer than that of PAF.…”
Section: Establishment Of Pafr-overexpressing Cells and Their Immediamentioning
confidence: 99%
“…Because C-PAF is slightly less potent than PAF regarding receptor binding of NP3 cells (data not shown), its metabolic stability might explain the effects different from those of PAF. Since PAF is rapidly inactivated by PAF acetylhydrolase in serum (37)(38)(39) and cytosol (40), its effect is relatively transient at low concentrations. Since C-PAF is resistant to enzymatic inactivation by virtue of the methylcarbamyl moiety at its sn-2 position, its half-life is much longer than that of PAF.…”
Section: Establishment Of Pafr-overexpressing Cells and Their Immediamentioning
confidence: 99%
“…10 Furthermore, previous reports have revealed that the polymorphism of pPAF-AH gene (PLA2G7) influences its activity. Miwa et al 11 discovered an autosomal recessive heredity form of pPAF-AH deficiency in Japanese families. Stafforini et al 12 investigated these pPAF-AH-deficient families and found a point mutation, T for G at position 994 in exon 9, which results in an amino acid substitution Phe for Val at residue 279 (994 G4T, V279F) at the active site of pPAF-AH.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of pPAF-AH was decreased about 50% in subjects with 279V/F 12 and completely abolished in subjects with 279F/F, 4% of healthy Japanese adults. 11 There have been several reports of a significant association between this polymorphism and atherosclerotic diseases such as coronary artery disease, 13 stroke 14 and atherosclerotic occlusive disease. 15 Although V279F is rare in Caucasians, other genetic mutations (R92H, I198T and A379V) have been described in European populations.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, this enzyme degrades atherogenic oxidized lipids (Steinbrecher and Pritchard 1989;Stremler et al 1989;Stafforini et al 1992), and deficiency of Lp-PLA2 is a predisposing factor for cardiovascular diseases in people of Japanese ethnicity. That predisposition is mainly due to the presence of a common mutant allele, V279F; homozygotes of the mutant allele comprise 0.04 of this population, although V279F has not been reported in Caucasians (Miwa et al 1988;Stafforini et al 1996b). Deficiencies of Lp-PLA2 in Japanese are associated with increased risk of stroke (Hiramoto et al 1997), coronary artery disease (Yamada et al 1998(Yamada et al , 2000, atherosclerotic occlusive disease (Unno et al 2000), and abdominal aortic aneurysms (Unno et al 2002).…”
Section: Introductionmentioning
confidence: 81%